Interprofessional communication with hospitalist and consultant physicians in general internal medicine: a qualitative study - Gotlib Conn Lesley; Reeves Scott; Dainty Katie; Kenaszchuk Chris; Zwarenstein Merrick (BMC, 2012)
Abstract Background Studies in General Internal Medicine [GIM] settings have shown that optimizing interprofessional communication is important, yet complex and challenging. While the physician is integral to interprofessional work in GIM there are often communication barriers in place that impact perceptions and experiences with the quality and quantity of their communication with other team members. This study aims to understand how team members' perceptions and experiences with the communication styles and strategies of either hospitalist or consultant physicians in their units influence the quality and effectiveness of interprofessional relations and work. Methods A multiple case study methodology was used. Thirty-one semi-structured interviews were conducted with physicians, nurses and other health care providers [e.g. physiotherapist, social worker, etc.] working across 5 interprofessional GIM programs. Questions explored participants' experiences with communication with all other health care providers in their units, probing for barriers and enablers to effective interprofessional work, as well as the use of communication tools or strategies. Observations in GIM wards were also conducted. Results Three main themes emerged from the data: [1] availability for interprofessional communication, [2] relationship-building for effective communication, and [3] physician vs. team-based approaches. Findings suggest a significant contrast in participants' experiences with the quantity and quality of interprofessional relationships and work when comparing the communication styles and strategies of hospitalist and consultant physicians. Hospitalist staffed GIM units were believed to have more frequent and higher caliber interprofessional communication and collaboration, resulting in more positive experiences among all health care providers in a given unit. Conclusions This study helps to improve our understanding of the collaborative environment in GIM, comparing the communication styles and strategies of hospitalist and consultant physicians, as well as the experiences of providers working with them. The implications of this research are globally important for understanding how to create opportunities for physicians and their colleagues to meaningfully and consistently participate in interprofessional communication which has been shown to improve patient, provider, and organizational outcomes.